Compact H-shaped microstrip antenna with shorting post using IE3D - Pandey A.; Singh A.K. (My University, 2025)
The characteristics of a small antenna using an H-shaped microstrip patch antenna is analyzed. Significant reduction of antenna size can be realized when the H-shaped patch is used instead of the conventional rectangular microstrip patch antenna.The effect of various antenna parameters like substrate height, radius of shorting post and feed point are analyzed and their effect on return loss is shown. © 2008 IEEE.